AIAA Scitech 2019 Forum 2019
DOI: 10.2514/6.2019-0822
|View full text |Cite|
|
Sign up to set email alerts
|

Performance Enhancement of Gust Load Alleviation Systems for Flexible Aircraft using HOptimal Control with Preview

Abstract: Most of the gust load alleviation systems (GLAS) of currently-operational aircraft are of feedback-only control architecture based on inertial measurements. In few other aircraft, aerodynamic measurements from air data sensors are additionally included, or presently considered for inclusion, as they usually result in improving the performance of the GLAS. In both sensor types, the control system has very little time to react; and therefore, the performance of the GLAS would be further enhanced if the turbulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 19 publications
(29 reference statements)
2
16
0
Order By: Relevance
“…A complete derivation of the preview control problem can be found in Ref. [40], which yields the discrete-time system given by Equation (9). This system is in the standard form of a control problem given by Equation (7), hence the characterisation of solvability relies exclusively on that of control theory.…”
Section: Preview Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…A complete derivation of the preview control problem can be found in Ref. [40], which yields the discrete-time system given by Equation (9). This system is in the standard form of a control problem given by Equation (7), hence the characterisation of solvability relies exclusively on that of control theory.…”
Section: Preview Controlmentioning
confidence: 99%
“…Each step of this procedure is then detailed in Subsection 4.2: Obtain the bare linear model of the aircraft Trim the non-linear model at the desired operating point Linearise the model at the trim point from the previous step Adjust the linear model to be in the standard form for control If not already defined in the original non-linear model, add the exogenous disturbance inputs (without delay) to the linear model Include the actuator/sensor dynamics, if not already defined in the original non-linear model Normalise and weight the performance channels Normalise the inputs and outputs of the performance channels to obtain an open-loop norm Add the appropriate input- and control-action weighting functions Obtain the discrete-time preview system model Discretise the model with an adequate sampling time Add a chain of h unit delays (explained in more detail in Ref. [40]) to obtain the discrete-time preview system model defined in Equation (9) Augment the measurement vector to include the previewed signal Proceed to the steps that a specific control design method may require (e.g. MATLAB’s or functions) …”
Section: Control Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In [3], the authors synthesized an H ∞ optimal controller for alleviating the structural loads and enhancing the ride qualities of a flexible aircraft. In their work, the controller was synthesized by two different methods of the H ∞ optimal control: full-order based on the work of [4,5], and fixedstructure based on the method presented in [6,7], and implemented in the MATLAB Robust Control Toolbox.…”
Section: Introductionmentioning
confidence: 99%